Utilization of primary and secondary biochemical compounds in cotton as diagnostic markers for measuring resistance to cotton leaf curl virus - Chauhan, Prashant; Mehta, Naresh; Chauhan, R. S.; Kumar, Abhishek; Singh, Harbinder; Lal, Milan Kumar; Tiwari, Rahul Kumar; Kumar, Ravinder (Frontiers in Plant Science, 2023)
Cotton (Gossypium hirsutum L.) is one of the most important staple fibrous crops cultivated in India and globally. However, its production and quality are greatly hampered by cotton leaf curl disease (CLCuD) caused by cotton leaf curl virus (CLCuV). Therefore, the aim of the present study was to investigate the biochemical mechanisms associated with CLCuD resistance in contrasting cotton genotypes. Four commercial cotton varieties with susceptible (HS 6 and RCH-134 BG-II) and resistant (HS 1236 and Bunty) responses were used to analyze the role of primary (sugar, protein, and chlorophyll) and secondary (gossypol, phenol, and tannin) biochemical compounds produced by the plants against infection by CLCuV. The resistant cultivars with increased activity of protein, phenol, and tannin exhibited biochemical barriers against CLCuV infection, imparting resistance in cotton cultivars.Reducing sugar in the healthy plants of the susceptible Bt cultivar RCH 134 BG-II exhibited the highest value of 1.67 mg/g at 90 days. In contrast, the lowest value of 0.07 mg g-1 was observed at 60 DAS in the highly diseased plants of the susceptible hybrid HS 6. Higher phenol content (0.70 mg g-1) was observed at 90 DAS in resistant cultivars, whereas highly susceptible plants exhibited the least phenol (0.25 mg g-1) at 90 DAS. The lowest protein activity was observed at 120 DAS in susceptible cultivars HS 6 (9.4 mg g-1) followed by RCH 134 BG-II (10.5 mg g-1). However, other biochemical compounds, including chlorophyll, sugar, and gossypol, did not show a significant role in resistance against CLCuV. The disease progression analysis in susceptible cultivars revealed non-significant differences between the two susceptible varieties. Nevertheless, these compounds are virtually associated with the basic physiological and metabolic mechanisms of cotton plants. Among the primary biochemical compounds, only protein activity was proposed as the first line of defense in cotton against CLCuV. The secondary level of defense line in resistance showed the activity of secondary biochemical compounds phenol and tannins, which displayed a significant increase in their levels while imparting resistance against CLCuV in cotton.